2007
DOI: 10.1002/marc.200600895
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Silver Nanoparticles by Polyelectrolytes and Poly(ethylene glycol)

Abstract: Silver nanoparticles of 23 nm size were formed by chemical reduction of silver nitrate in excess of aqueous sodium borohydride. To examine the aggregation behavior in NaCl solutions, they were coated with poly(diallyldimethylammonium chloride), poly(allylamine hydrochloride) and poly(ethylene glycol) by layer‐by‐layer assembly. Silver nanoparticles coated with PDADMAC of both high and low molecular weight revealed the lowest stability independent of salt concentration. Silver nanoparticles coated with PAH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 54 publications
2
58
0
Order By: Relevance
“…It can be seen that all spectra have one absorbance peak around 400 nm. These absorption peaks known as surface plasmon resonance of silver nanopartciles have been presented in many literature [11][12][13]. The optical spectral feature confirms that the silver nanoparticles are formed in the liquid.…”
Section: Resultssupporting
confidence: 59%
“…It can be seen that all spectra have one absorbance peak around 400 nm. These absorption peaks known as surface plasmon resonance of silver nanopartciles have been presented in many literature [11][12][13]. The optical spectral feature confirms that the silver nanoparticles are formed in the liquid.…”
Section: Resultssupporting
confidence: 59%
“…[40,41] Also, using direction-specific release [42] and anisotropic [43] and anisotropic multicompartment [44] capsules it should be possible targeting cellular organelles. We also note that cell culture studies reported in this work will be useful for developing delivery systems for in vivo applications and studying their response.…”
Section: Resultsmentioning
confidence: 99%
“…Significant advantages of this method over previous ones include: it has a short reaction time; small and relatively uniform particles with a diameter less than 10 nm are produced; the reaction proceeds rapidly at room temperature; organic solvents are not used; and the resulting particles are easily separated from the reaction mixture. In previous methods [12][13][14][15][16][17][18][19][20][21], it is difficult to obtain pure silver nanoparticles of very small size under mild reaction condition and with convenient operation to separate silver nanoparticles from the reaction mixture. In contrast, our new method allows uniform silver nanoparticles with high purity and diameters around 5 nm to be prepared easily.…”
Section: Discussionmentioning
confidence: 99%
“…Various reducing agents (e.g., sodium tetrahydridoborate, hydrazine, ethanol, ethylene glycol, and ascorbic acid), dispersant (e.g., polyvinylpyrrolidone (PVP), and polyethylene oxide) have been used in nanoparticle preparation [10][11][12][13][14][15][16][17][18][19][20][21]. For example, Radziuk et al prepared silver nanoparticles by reduction of silver nitrate in an excess of aqueous NaBH 4 , obtaining nanoparticles with a diameter of 20 nm [16]. Tan et al synthesized silver nanoparticles by reduction of silver nitrate using potassium bitartrate at 100°C for 2 h [17].…”
Section: Introductionmentioning
confidence: 99%